Derajat Toksisitas Trombosit pada Penderita Kanker Kolorektal yang Mendapat Kemoterapi CapeOX - Yusmaidi Yusmaidi; Rakhmi Rafie; Muhammad Nur; Bilqis Nabilah (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Colorectal cancer treatment one of which is chemotherapy. One of the regimens/chemotherapy medicine is CapeOX (Capecitabine + Oxaliplatin). The use of oxaliplatin which is platinum-based chemotherapy has side effects in the form of hematological toxicity (myelosuppression) one of which is platelet count. Thrombocytopenia is a platelet count of less than 100,000 / mm3this is one of the hematological toxicity that can be found in colorectal cancer patients who received chemotherapy. Research Objective: The purpose of this study was to determine the difference average of platelet levels and pre and post-chemotherapy CapeOX and the form of the degree of platelet toxicity in colorectal cancer patients receiving CapeOX chemotherapy.Method: This study is a historical (retrospective) cohort. The sample of this study was 70 patients obtained from a consecutive sampling calculation. Data analysis using Paired T-Test.Results: The age of colorectal cancer patients ranged from 18 to 73 years, with the highest frequency of 56-65 (38.6%), comparison of female 34 (48.6%) and male 36 (51.4%). The most widely used type of surgery was a Low Anterior Resection of 40 (57.1%). In this study, the highest decrease in platelet levels occurred in the sixth series of 54.186/mm3 with a standard deviation of 16.127/mm3. There was a decrease in average platelet levels highest occurred in the sixth cycle of 54,186 / mm3 with a standard deviation of 16,127 / mm3, and obtained first-degree platelets) toxicity in the 5th and 6th cycles of 3 (4.3%) and 18 (25.7) and who experienced second degree in the 5th and 6th cycles of 1 (1.4%) and 10 (14.3%).